Design and Build Telecontroling Temperature and Water Quality of Turtle Aquascapes Based on Fuzzy Logic - Ayyubi, Amar Farrichil; Imammuddin, Azam Muzakhim; Kusumawardani, Mila (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
Aquascape is one of the media for water pets that is quite popular during the pandemic. One of the animals that can be kept with aquascape media is a turtle. Maintenance of turtles in aquascapes requires accuracy and persistence in maintaining water quality in aquascapes to have stable conditions for turtles in them. Temperature, turbidity and water level are some of the parameters that need to be considered in order for turtles to survive in the aquascape. Thus, we need a technology that has a function as a monitoring of temperature, turbidity and water level as well as having a direct connection to the user. In this study, the use of the DS18B20 temperature sensor, water turbidity sensor and ultrasonic sensor as a water level meter has a connection that is connected to the user using ESP32. In addition, the existence of pumps, filters and water coolers can support the quality of water in the aquascape to be maintained either automatically or manually. The results of this study indicate that the existence of this system can maintain the quality of water in the aquascape in real time to the user. This is demonstrated by three sensors that have a 98% accuracy level so that it can turn on the output components well. The three sensors also have delays of 240.006315 ms and are in the category